133 Cardiopulmonary exercise testing: does ethnicity matter?. (5th June 2017) - Prakash, Keerthi; Papatheodorou, Stathis; Ensam, Bode; Miles, Chris; Azizi, Saeed; Bulleros, Paulo; Fanton, Zephryn; Malhotra, Aneil; D'Silva, Andrew; Finocchiaro, Gherardo; Keteepe-Arachi, Traceey; Tome, Maite; et al.
Abstract : Introduction: Hypertrophic cardiomyopathy (HCM) is the largest cause of sudden cardiac death in athletes. Differentiation between HCM and athletic cardiac adaptation is not always straightforward. Cardiopulmonary exercise testing (CPET) is useful in this context, with a peak VO2 >120% predicted commonly used to differentiate athletes with HCM from those with physiological left ventricular hypertrophy. This value however is derived from a predominantly white population. Differences with ethnicity have been well documented on the ECG and echocardiogram of both athletes and individuals with HCM, however, ethnic differences in their physiology have not been well investigated to date. Purpose: To assess if there is a significant difference on CPET in HCM patients of black and white ethnicity. Methods: Cardiopulmonary exercise testing data was prospectively and retrospectively analysed from a cohort of 49 sedentary HCM patients assessed in a quaternary referral centre (36 white, 38 male; aged 15–65 years). Inclusion criteria: HCM patients of black or white ethnicity, NYHA 1, resting LVOT gradient<40 mmHg, no ICD in-situ and having completed a maximal CPET (defined as: R 1.1 and test terminated due to breathlessness/muscular fatigue). Results: Statistical significance was assessed using the Mann-Whitney U test (for non-parametric data) and the Student's T-test (for parametric data). Statistically significant differences between black and white HCM patients were noted in the% predicted peak power and% predicted peak VO2 /kg. (Table 1) Conclusion: Black HCM patients achieve a significantly lower% predicted peak power on CPET (24% lower) compared with white HCM patients. Black HCM patients also demonstrate a significantly lower% predicted peak VO2 /kg (10% lower) compared to white HCM patients. Larger studies are required to corroborate these ethnic differences, however, this study suggests that the current standard cut-off of a peak VO2 >120% predicted may be too high for a black athlete resulting in a false positive diagnosis of HCM.